2017
DOI: 10.1088/1478-3975/aa7c1e
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quorum sensing onto neural networks to understand collective decision making in heterogeneous microbial communities

Abstract: Microbial communities frequently communicate via quorum sensing (QS), where cells produce, secrete, and respond to a threshold level of an autoinducer (AI) molecule, thereby modulating gene expression. However, the biology of QS remains incompletely understood in heterogeneous communities, where variant bacterial strains possess distinct QS systems that produce chemically unique AIs. AI molecules bind to 'cognate' receptors, but also to 'non-cognate' receptors found in other strains, resulting in inter-strain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…While the modelling approach based on individual cells pursued here is very flexible and can accommodate many different features, approaches based on differential equations for chemical concentrations have the advantage that, at least in some limits, analytical solutions can be obtained 26,47 . In addition to these two strategies network-based approaches have been suggested 96 . We finally note that some of the results observed here may have relevance in morphogen-gradient based problems, in which the spatial distribution of the concentration of stimulating molecules can trigger a certain response of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While the modelling approach based on individual cells pursued here is very flexible and can accommodate many different features, approaches based on differential equations for chemical concentrations have the advantage that, at least in some limits, analytical solutions can be obtained 26,47 . In addition to these two strategies network-based approaches have been suggested 96 . We finally note that some of the results observed here may have relevance in morphogen-gradient based problems, in which the spatial distribution of the concentration of stimulating molecules can trigger a certain response of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Rudge et al observed the emergence of striking fractal patterns in growing colonies of E. coli [48]. Physical models such as the Hopfield model have also been implemented to predict how the capacity for groups of cells to make decisions scales with the number of cell types [44]. In the spirit of these observations, here we have identified that disrupting the long-range communication of a quorum sensing microbe through interference by a degrader strain yields complex physical behavior characteristic of a percolation transition.…”
Section: Discussionmentioning
confidence: 70%
“…With the recent advances in systems and molecular biology, many new studies are being conducted to understand the complex behaviors of microbes that arise due to cellular and spatial heterogeneity [9,[26][27][28][41][42][43][44]. Several studies have shown that many cellular systems exhibit emergent phenomena previously studied in non-biological contexts and that can be explained using physical and statistical mechanical rules [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the interaction weight between strains, we constructed a mathematical model. The model is based on a set of differential equations and accounts for signal crosstalk by introducing a crosstalk weight for each pair of receptor and signal, similar to models used previously [5,34]. Specifically, the expression of the QS-regulated gene lacZ follows: where the effective concentration of signal as the result of crosstalk is, …”
Section: Resultsmentioning
confidence: 99%
“…Interactions between network components influence state dynamics and are represented as weights, with the magnitude of the weight indicating the strength of the interaction and the sign of the weight indicating whether the interaction promotes or inhibits activation. We have previously implemented a neural network to theoretically analyze the information capacity within a QS networks composed to multiple Staphylococcus aureus strains [34]. Here we extend these ideas, combining both experimental and theoretical results, to test whether neural network models can be used to predict and control the activation of QS in communities of bacteria producing multiple signals.…”
Section: Introductionmentioning
confidence: 99%